STRATEGI PENINGKATAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA YANG BERKELANJUTAN - Sari, Nurmita; Parawu, Hafiz Elfiansyah; Taufik, Ahmad (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
This research aims to determine strategies for increasing community participation in the development of Ilan Batu Uru Village, West Walenrang District, Luwu Regency. The research method used in this research is a qualitative research method, which is a form of research that aims to understand and describe phenomena regarding strategies for increasing community participation in village development by analyzing behavior, perceptions, interests, motivations, actions, by presenting data descriptively in the form of words or language. The research results show that the strategy to increase community participation in increasing community participation is quite good. However, it needs to be improved further to be more optimal, this can be seen from the aspects of planning, implementation and supervision.